Mental health trajectory throughout high school football career: a four-year prospective cohort study - Buddenbaum, Claire V.; Recht, Grace O.; Sweeney, Sage H.; Steinfeldt, Jesse A.; Ellis, Gage; Zuidema, Taylor R.; Kercher, Kyle A.; Bazarian, Jeffrey J.; Newman, Sharlene D.; Kawata, Keisuke (Frontiers in Psychiatry, 2025)
IntroductionRepetitive head impacts may contribute to long-term neurological disorders, including chronic traumatic encephalopathy (CTE), and mental health decline often precedes cognitive symptoms. Adolescent athletes are especially vulnerable, yet prospective data on mental health trajectory across high school athletic career are limited.AimTo examine the mental health changes of high school football players across multiple seasons of participation.MethodsThis prospective cohort study included 6 high schools across southern Indiana for 4 consecutive seasons from July 2021 to February 2025. Participants included male high school football players and noncontact athletes (ages 13-18) in tennis, cross-country, and swimming. Sensor installed mouthguards were utilized to measure head impacts and surveys were conducted pre and post season to assess anxiety and depressive symptoms.ResultsA total of 371 adolescent athletes participated in this longitudinal study, including 275 high school football players (mean [SD] age, 15.3 [1.2] years) and 96 non-contact control athletes (mean [SD] age, 15.9 [1.2] years), with varying lengths of participation across 4 years of study. Depression and anxiety symptoms remained consistent across 1 season (pre vs. postseason) in both groups, as illustrated by non-significant group by time interaction in PHQ-9 [b=-0.11, 95%CI(-0.98, 0.76), p=0.814] or GAD-7 [b=0.09, 95%CI(-0.62, 0.79), p=0.806]. The same pattern was observed for those who participated in 2 consecutive seasons [PHQ-9 b=-0.01, 95%CI (-0.96, 0.98), p=0.980; GAD-7 b=0.42, 95%CI(-0.43, 1.27), p=0.33]. However, among those with 3 consecutive years of participation, there was significant seasons (pre vs. post) by year (1st vs. 3rd year) interaction in depression symptoms in the football group [PHQ-9: b=1.50, 95%CI (0.32, 2.66), p=0.015], a pattern not observed in the control group.DiscussionOur data suggest that mental health wellbeing remain consistent across 1 to 2 years of high school sports participation, regardless of head impact exposure or types of sports they play (football or non-contact sports). However, psychological burden may accumulate over multiple years of football participation.